(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2025)
This article analyzes the essence of integro-differential equations, their role in mathematical modeling, and their significance for describing physical, technical, and biological processes. Integro-differential equations represent a class of complex equations that combine differential and integral operations. The article discusses their main types, solution methods, and the advantages of analytical and numerical approaches. The influence of the integral kernel and boundary conditions on the equation’s solution is also theoretically substantiated